DNA interaction of ruthenium(ii) complexes with imidazo[4, 5-f][1, 10]phenanthroline derivatives. Issue 12 (28th February 2019) - Yu, Bole; Rees, Thomas W.; Liang, Jiewen; Jin, Chengzhi; Chen, Yu; Ji, Liangnian; Chao, Hui
Abstract : The DNA interaction properties of four Ru(ii ) complexes with imidazo[4, 5- f ][1, 10]phenanthroline derivatives were investigated by spectral titration, gel electrophoresis (GAR), dynamic light scattering (DLS), zeta potential, atomic force microscopy (AFM), and transmission electron microscopy (TEM). Abstract : In this paper, the DNA interaction properties of four Ru(ii ) polypyridyl complexes, [Ru(bpy)2 (pip)] 2+ (1 ), bpy = 2, 2′-bipyridine, pip = 2-phenyl-imidazo[4, 5- f ][1, 10]phenanthroline, [Ru(bpy)2 (nip)] 2+ (2 ), nip = 2-naphthyl-imidazo[4, 5- f ][1, 10]phenanthroline, [Ru(bpy)2 (aip)] 2+ (3 ), aip = 2-(9-anthryl)-imidazo[4, 5- f ][1, 10]phenanthroline and [Ru(bpy)2 (pyip)] 2+ (4 ), pyip = 2-(1-pyrenyl)-imidazo[4, 5- f ][1, 10]phenanthroline, were investigated by spectral titration. The intensity increases in the MLCT band of the complexes and the decrease in absorption due to the DNA secondary structure was attributed to DNA condensation by these complexes. The DNA condensing behavior of these complexes was investigated in more detail by gel electrophoresis (GAR), dynamic light scattering (DLS), zeta potential, atomic force microscopy (AFM), and transmission electron microscopy (TEM). The results suggest that the concentration of the complex plays a critical role in its DNA intercalating and DNA condensing behavior. Meanwhile, the aryl units in the ligands of complex1–4 also have a large effect on their interactions with DNA.